1993
DOI: 10.1523/jneurosci.13-02-00455.1993
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the adult retina with microglia-suppressing factors retards axotomy-induced neuronal degradation and enhances axonal regeneration in vivo and in vitro

Abstract: To monitor the cascade of events initiated by injury of adult neurons, and to explore whether and how neighboring microglial cells contribute to the degradation of lesioned neurons, axotomy-induced ganglion cell degeneration was investigated in adult rats. Suppression of macrophage and microglia activity during the weeks following transection of the optic nerve was performed with the immunoglobulin-derived tripeptide Thr-Lys-Pro, which is a macrophage inhibitory factor (MIF) and retards the activity of cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
154
1
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(166 citation statements)
references
References 52 publications
8
154
1
3
Order By: Relevance
“…The results presented above, however, indicate that two different cell types, ganglion cells and microglial cells (73), contribute to the origin of tPA in the retina. Although the exact reason why microglial cells synthesize tPA after KA injection is not clear, they might synthesize tPA and use it to migrate into the inner retina to remove the debris from dying cells (74)(75)(76) but they can contribute also to secondary retinal damage. It is also possible that microglial cells can be migrated into the inner retina independent of tPA up-regulation (32,73,77).…”
Section: Discussionmentioning
confidence: 99%
“…The results presented above, however, indicate that two different cell types, ganglion cells and microglial cells (73), contribute to the origin of tPA in the retina. Although the exact reason why microglial cells synthesize tPA after KA injection is not clear, they might synthesize tPA and use it to migrate into the inner retina to remove the debris from dying cells (74)(75)(76) but they can contribute also to secondary retinal damage. It is also possible that microglial cells can be migrated into the inner retina independent of tPA up-regulation (32,73,77).…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglia have been implicated in demyelinating and neurodegenerative diseases (Itagaki et al, 1989;Lucchinetti et al, 2000;McGeer and McGeer, 2003). There is some experimental support for the proposal that blocking microglia activation may be neuroprotective, for example through the production of trophic factors including NGF and NT3 (Mallat et al, 1989;Thanos et al, 1993;Elkabes et al, 1996;Rabchevsky and Streit, 1997;Lim et al, 2000;Wu et al, 2002;Zhang et al, 2003). Furthermore, the observation that TNF-␣ null mice show increased neuronal death after ischemia in association with reduced microglia recruitment is consistent with microglia-mediated neuroprotection detectedonmicrogliainthecontrollesion(F,H).AfterLPSinjection,Npn-1-andPlexin-1-positivestainingispresentinactivatedmicroglia(G,I).…”
Section: Microglia-neuron Interaction: a Role For Semaphorinmentioning
confidence: 99%
“…Their role is not restricted to a mere removal of damaged and dying neurons. Microglia contribute actively to the degradation of neurons, because it has been shown that suppression of microglial activity results in a retardation of tissue cell death (Thanos et al, 1993;Frade and Barde, 1998).…”
Section: Identification Of Retinal Cell Types Expressing Permeabilizimentioning
confidence: 99%